"The Fathers have eaten Sour Grapes, and the Children's Teeth are set on Edge": Differentiating the Emotional Experiences of Grima and Disgust - Schweiger Gallo, Inge; Rodríguez Monter, Miryam; Álvaro-Estramiana, José Luis; Durán, Juan Ignacio (Spanish Journal of Psychology, 2019)
The Spanish term grima refers to the aversive emotional experience typically evoked when one hears, for example, a scratch upon a chalkboard. Whereas Spanish speakers can distinguish between the concepts of grima and disgust, English and German speakers lack a specific word for this experience and typically label grima as disgust. In the present research, we tested the degree of differentiation between the two aversive experiences in Spanish speakers. Study 1 addressed whether Spanish speakers apply spontaneously the term grima rather than disgust to grima-eliciting experiences. Study 2 systematically addressed the constitutive features of both grima and disgust by mapping their internal structures. Results showed that the noise of a chulk on a blackboard and scraping fingernails on a blackboard, along with the physical manifestation of goose bumps, were the most typical features of the category. Whereas both grima and disgust were characterized as unpleasant sensations, t(193) = 1.21, ns, they differed with respect to their physiological signatures (e.g., producing shivers was characteristic of grima, as compared to disgust, t(194) = 12.02, p = .001, d = 1.72) and elicitors (e.g., a fractured bone was a characteristic elicitor of grima; t(193) = 5.78, p = .001, d = .83, whereas pederasts and pedophiles were the most characteristic elicitor of disgust, t(193) = 8.46, p = .001, d = 1.21). Thus, both grima and disgust are conceptually different experiences, whose shared features hold different degrees of typicality. The present research suggests that grima and disgust are two distinct emotion concepts.
Keywords: disgust; emotion concept; emotional experience; grima; JCR; Scopus